Breast cancer is a threatening scenario resulting from the development of endometriosis and benign breast disease overlap syndrome: literature review - T.A. Lunko; O.O. Lytvynenko; A.S. Lunko; S.V. Konovalenko; A.V. Khmel (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. According to the National Cancer Registry of Ukraine, mortality from breast cancer (BC) continues to be at the first places in the structure of oncological pathology among the female population. The overlap syndrome of genital endometriosis (GE) and benign breast disease (BBD) can play a significant role in the development of BC. The purpose: using data from modern literature sources, to consider the overlap syndrome of GE and BBD as a precancerous pattern in the development of BC and outline possible steps to solve the problem. Materials and methods. The search and selection of publications was carried out in the PubMed and Google Scholar databases using the following terms: genital endometriosis, benign breast disease, mastopathy, fibrocystic dysplasia, mastalgia, breast cancer, hormone therapy. Results. A convincing link between endometriosis and fibrocystic disease has been established in fertile women: the prevalence of BBD in patients with endometriosis is 36–38 %. Pilot clinical studies have confirmed that in women with endometriosis who received dienogest at a dose of 20 mg/day orally for 24 weeks, a significant decrease in breast size (p < 0.023) and regression of mastopathic changes were observed when assessing the effect of progestogen on the breast using ultrasound. A slight decrease (p = 0.089) in the maximum diameter of the ducts was observed. At the stages of development of the overlap syndrome of GE and BBD with a confirmed increased risk of BC, a complex pathogenetic matrix is formed, the processes in which are often not linear, but can occur in parallel, demonstrating the diversity and unpredictability of biological events. The high percentage of overlap syndrome of GE and BBD confirms the idea of the unity of the origin of pathological changes in target organs and the synchronous development of benign hyperplastic processes in them. Conclusions. It is advisable to consider hyperplastic diseases as a generalized process in the reproductive system, and to develop single therapeutic tactics when gynecological pathology is combined with breast diseases. The overlap syndrome of GE and BBD, which is a proven factor of increased risk of breast cancer, requires responsible and coordinated teamwork of endocrinologists, mammologists and obstetricians-gynecologists, which is designed to create necessary conditions for a significant improvement in the effectiveness of therapy. The development in the near future of an algorithm for clinical monitoring of patients with overlap syndrome of GE and BBD will be a logical and justified step, because early diagnosis of BC provides better treatment results and an increase in the quality of life of patients.